Breeding performance and the effect of stocking density on the growth and survival of climbing perch, Anabas testudineus. - Ibrahim, Zalina; Saad , Che Roos; Abd Rahim, Abdullah; Christianus, Annie; Harmin, Sharr Azni (Academic Journals, 2011)
Anabas testudineus was successfully induced to spawn using LHRHa. Egg production, hatching rate and GSI were 5126 eggs/fish, 62 and 10.41%, respectively. Results showed that the survival and growth of A. testudineus during the 30-day nursing period were stocking density dependent. The highest survival rate was recorded in T1 (35/L; 75%), followed by T2, (55/L; 53%) and lastly T3 (75/L; 43%). The weekly growth performance in T1 (35/L), in terms of total body length and body weight was significantly better than other treatments, especially after 21-day of nursing. Fish larvae were fed with a combination of live and prepared foods. Water quality parameters were stable and not influenced by the stocking densities tested.